ROSUS 2017: računalniška obdelava slik in njena uporaba v Sloveniji 2017 : (zbornik 12. strokovne konference) - Marina Bajić; Potočnik, Božidar (2017)
ROSUS 2017 : Computer Image Processing and Its Application in Slovenia 2017 : Proceedings of the 12th Professional Conference. ROSUS 2017–Computer image processing and its application in Slovenia 2017 is a professional conference that, since 2006, has been organized every year by the Institute of Computer Science of the Faculty of Electrical Engineering and Computer Science, University of Maribor. The conference connects researchers in the fields of Image Processing and Machine Vision with users of this knowledge, whereby users are coming from diverse industrial environments, Biomedicine, Sport, Entertainment, and related fields. The proceedings of ROSUS 2017 combine 12 scientific articles by 21 authors, including four invited lectures. Contributions represent the latest achievements of Slovenian experts in the fields of Image Processing and Vision, and also highlight trends and novelties in these areas. Great emphasis is on promotion of the economic usefulness of Image Processing and Vision applications in the Slovenian region. Namely, such software, due to high precision, robustness, and exceptional speed in information processing, provides new opportunities for penetration on the high technologies market.
Keywords: knowledge transfer; Computer Image Processing; Machine Vision; Biomedicine; industrial applications